1999
DOI: 10.1074/jbc.274.2.859
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete Three-amino Acid Segment (LVI) at the C-terminal End of Kinase-impaired ErbB3 Is Required for Transactivation of ErbB2

Abstract: ErbB3 is unique among other members of the receptor tyrosine kinase family of growth factor receptors in that its kinase domain is enzymatically impaired. This renders it incapable of transducing a signal in response to ligand binding. However, in conjunction with ErbB2, ErbB3 is a potent mediator of signaling by the growth factor heregulin. Heregulin binding to ErbB3 induces formation of a heterodimeric complex with ErbB2, and this results in transactivation of the ErbB2 kinase. Although interaction between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…(3) There are three sequential amino-acid residues in this region, Leu 957 , Val 958 and Ile 959 , that are required for transactivation of ERBB2 and that are conserved among EGFR, ERBB3 and ERBB4, whereas ERBB2 differs at the position equivalent to site 957. 61 (4) The same amino-acid substitutions at positions 931, 934 and 966 of ERBB3, relative to the other ERBBs, in three diverse species (human, rat and pufferfish) indicate potential functional significance. 41 (5) The carboxy terminal region of ERBB3 includes 13 tyrosines and the sequence Tyr-Glu-Tyr-Met is repeated three times.…”
Section: The Erbb3 Protein Primary and Crystal Structurementioning
confidence: 96%
See 1 more Smart Citation
“…(3) There are three sequential amino-acid residues in this region, Leu 957 , Val 958 and Ile 959 , that are required for transactivation of ERBB2 and that are conserved among EGFR, ERBB3 and ERBB4, whereas ERBB2 differs at the position equivalent to site 957. 61 (4) The same amino-acid substitutions at positions 931, 934 and 966 of ERBB3, relative to the other ERBBs, in three diverse species (human, rat and pufferfish) indicate potential functional significance. 41 (5) The carboxy terminal region of ERBB3 includes 13 tyrosines and the sequence Tyr-Glu-Tyr-Met is repeated three times.…”
Section: The Erbb3 Protein Primary and Crystal Structurementioning
confidence: 96%
“…Studies with transfected mutants of ERBB3 and ERBB2 appeared to rule out participation of ERBB3 as a kinase and of another cytoplasmic kinase. 61 It is most likely that allosteric interactions between lobes of the kinase regions of ERBB2 and ERBB3 result in activation of ERBB2. 8 (2) The C-terminal domain of ERBB3 is 30 to 50% longer than the comparable regions of EGFR and ERBB2.…”
Section: The Erbb3 Protein Primary and Crystal Structurementioning
confidence: 99%
“…We demonstrated that the combination of ErbB-3 with ErbB-2 was much more potent in the induction of cell spreading than ErbB-3/ErbB-1. ErbB-3 can eciently transactivate the kinase activity of the`orphan' receptor ErbB-2; a speci®c motif, LVI, localized at the impaired kinase domain of ErbB-3 is required for this transactivation (Schaefer et al, 1999). Truncated ErbB-3 receptors, preserving this LVI motif can transactivate ErbB-2, which in turn leads to phosphorylation of ErbB-3 receptor itself (Schaefer et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…ErbB-3 can eciently transactivate the kinase activity of the`orphan' receptor ErbB-2; a speci®c motif, LVI, localized at the impaired kinase domain of ErbB-3 is required for this transactivation (Schaefer et al, 1999). Truncated ErbB-3 receptors, preserving this LVI motif can transactivate ErbB-2, which in turn leads to phosphorylation of ErbB-3 receptor itself (Schaefer et al, 1999). In our experiments we observed that the DCT-ErbB-3 receptor, lacking the C-terminal region downstream from the kinase domain but preserving LVI motif, can mediate some signaling eects, in particular, MAP kinase activation.…”
Section: Discussionmentioning
confidence: 99%
“…This motif is necessary for ligand-independent dimerization of EGFR intracellular domains (12) and for transphosphorylation in ErbB2/ErbB3 heterodimers (13). Moreover, alanine substitutions in this region override mutations in the transmembrane segment of ErbB2 that would otherwise lead to constitutive signaling via non-ligand induced dimerization (14).…”
mentioning
confidence: 99%